Social capital : evolution, contestation, application and digitization - Singh, Mudit Kumar (Emerald points., 2024)
Is our understanding of social capital consistent with development interventions and the digital world? Social Capital: Evolution, Contestation, Application and Digitization delves into the intricacies of social capital and its digital dimensions, examining its historical evolution, contemporary contestation and practical applications. Introducing a refurbished conceptualization of social capital, Mudit Kumar Singh introduces case studies from both the Global North and the Global South, including the USA, the UK, Europe, India, Latin America and Africa to build a sound understanding of social capital and its evolution in the age of social media and online community. Critically examining the debates and controversies surrounding the concept, forms and application of social capital, Dr. Singh briefly discusses how social capital has been used for positive social change, including its role in civic engagement and economic welfare. Highlighting successful examples of its application in development interventions, chapters also explore the darker sides of social capital in the digital era, including the spread of misinformation, echo chambers and online polarization, before turning to its positive influence in the digital realm. Providing practical recommendations for leveraging social capital for social good, this is a valuable, thought-provoking and timely exploration of the multifaceted concept of social capital in the context of the digital revolution.